Potential role of glutathione in evolution of thiol-based redox signaling sites in proteins - Mohanasundaram, Kaavya A.; Haworth, Naomi L.; Grover, Mani P.; Crowley, Tamsyn M.; Goscinski, Andrzej; Wouters, Merridee A. (Frontiers in Pharmacology, 2015)
Cysteine is susceptible to a variety of modifications by reactive oxygen and nitrogen oxide species, including glutathionylation; and when two cysteines are involved, disulfide formation. Glutathione-cysteine adducts may be removed from proteins by glutaredoxin, whereas disulfides may be reduced by thioredoxin. Glutaredoxin is homologous to the disulfide-reducing thioredoxin and shares similar binding modes of the protein substrate. The evolution of these systems is not well characterized. A redox buffer, glutathione is conjugated to reactive cysteine of endogenous proteins, inducing conformational changes in the substrates, and affecting a signaling cascade. If a second cysteine is introduced into the sequence, the potential for disulfide formation exists. In favourable protein contexts, a bistable redox switch may be formed. Because of glutaredoxins similarities to thioredoxin, the mutated protein may be immediately exapted into the thioredoxin-dependent redox cycle upon the addition of the second cysteine. Here we searched for examples of protein substrates where the number of redox-active cysteine residues has changed throughout evolution. We focused on cross-strand disulfides (CSDs), the most common type of forbidden disulfide. We searched for proteins where the CSD is present, absent and also found as a single cysteine in protein orthologs. Three different proteins were selected for detailed study - CD4, ERO1 and AKT. We created phylogenetic trees, examining when the CSD residues were mutated during the protein evolution. We posit that the primordial cysteine is likely to be the active cysteine of the CSD attacked by thioredoxin. Thus a redox-active disulfide may be introduced into a protein structure by stepwise mutation of two residues in the native sequence to Cys. By extension, evolutionary acquisition of structural disulfides in proteins can potentially occur via transition through a redox-active disulfide state.